English Vocabulary Mastery Profile of STIS Harsy Central Lombok Students - Sudiani, Sudiani (Reflection Journal, 2024)
This study explores the English vocabulary mastery profile of fifth-semester students in the Family Law Program at STIS Harsy, Central Lombok. The primary objective is to identify students' vocabulary proficiency levels, as vocabulary is a key foundation for productive language skills. Using a descriptive research method, the study evaluates the vocabulary skills of all students within the specified group through a multiple-choice vocabulary mastery test. Results categorize student vocabulary proficiency into three levels: "Not Good" (43.33%), "Poor" (30.00%), and "Good" (26.67%). The significant portion of students in the "Not Good" category highlights the need for instructional interventions to enhance vocabulary knowledge, essential for effective communication in academic settings. Conclusions indicate that targeted teaching methods, including explicit instruction, cooperative learning, and digital tools, are recommended to address vocabulary deficiencies. Implementing these strategies can foster independent vocabulary acquisition and improve overall language skills, enabling students to participate more actively in academic contexts.